2013
DOI: 10.1007/s12272-013-0210-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambroxol inhibits rhinovirus infection in primary cultures of human tracheal epithelial cells

Abstract: The mucolytic drug ambroxol hydrochloride reduces the production of pro-inflammatory cytokines and the frequency of exacerbation in patients with chronic obstructive pulmonary disease (COPD). However, the inhibitory effects of ambroxol on rhinovirus infection, the major cause of COPD exacerbations, have not been studied. We examined the effects of ambroxol on type 14 rhinovirus (RV14) infection, a major RV group, in primary cultures of human tracheal epithelial cells. RV14 infection increased virus titers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
0
26
0
8
Order By: Relevance
“…1,2 Ambroxol has also been reported to have rhinovirus infection inhibition 3 and perioperative lung protection effects. 4 Recently, the increasement of glucosylceramidase activity and reduction of markers of oxidative stress in cells treated with ambroxol suggested that ambroxol may offer a potential treatment for Parkinson's disease.…”
Section: Ambroxol Trans-4-(2-amino-35-dibromobenzylamino)-cyclo-mentioning
confidence: 99%
“…1,2 Ambroxol has also been reported to have rhinovirus infection inhibition 3 and perioperative lung protection effects. 4 Recently, the increasement of glucosylceramidase activity and reduction of markers of oxidative stress in cells treated with ambroxol suggested that ambroxol may offer a potential treatment for Parkinson's disease.…”
Section: Ambroxol Trans-4-(2-amino-35-dibromobenzylamino)-cyclo-mentioning
confidence: 99%
“…Стагнация дренажной функции способствует ко-лонизации микроорганизмами, усугублению вос-палительного процесса, развитию бронхиальной обструкции, вентиляционно-перфузионных наруше-ний и формированию оксидативного стресса. Из-быток бронхиального секрета снижает активность местного иммунитета, в частности подавляется синтез секреторного IgА [15,18]. Вязкость, эластич-ность, адгезивность бронхиального секрета опре-деляют возможность свободного его отделения, по-этому роль муколитических лекарственных средств в лечении бронхита является столь же важной, сколь Рис.…”
Section: заключениеunclassified
“…В качестве индуцирующего острый бронхит аген-та использовали 1 % раствор формалина [15,18], который вводили эндотрахеально эксперименталь-ным и контрольным животным с помощью зонда для эндотрахеального введения модели IA-1B-R (PennCentury Inc., USA) на фоне легкого наркоза «Золети-лом» (Virbac S.A., Франция) в дозе 2,6 мг/кг.…”
Section: Introductionunclassified
“…В ходе исследования показано, что амброксол способен уменьшать выброс гистами-на из тучных клеток под воздействием различных им-мунных и неиммунных стимулов, тем самым влияя на развитие реакции гиперчувствительности немед-ленного типа [31]. Воздействуя на базофилы, моно-циты и нейтрофилы, амброксол влияет на позднюю фазу воспаления, в том числе и в тканях за предела-ми легких [32,33]. В базофилах амброксол ингиби-рует не только высвобождение гистамина, но и об-разование IL-1 и IL-3.…”
Section: обзоры литературыunclassified
“…В ус-ловиях эксперимента на культуре клеток было до-казано, что амброксол ингибирует развитие ринови-русной инфекции (RV14), способствует уменьшению уровня молекул межклеточной адгезии-1 (ICAM-1), кислых эндосом путем торможения активации транс-крипционного фактора NF-κB. Выявлен противовос-палительный эффект препарата в виде уменьшения продукции цитокинов (IL-1β, IL-6, IL-8) при рино-вирусной инфекции [33].…”
Section: обзоры литературыunclassified